1999
DOI: 10.1046/j.1365-2958.1999.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic, glycosyl transferase and acyl transferase modules of the cell wall peptidoglycan‐polymerizing penicillin‐binding protein 1b of Escherichia coli

Abstract: SummaryThe penicillin-binding protein (PBP) 1b of Escherichia coli catalyses the assembly of lipid-transported Nacetyl glucosaminyl-b-1,4 -N-acetylmuramoyl-L-alanyl-g-D-glutamyl-(L)-meso-diaminopimelyl-(L)-D-alanyl-D-alanine disaccharide pentapeptide units into polymeric peptidoglycan. These units are phosphodiester linked, at C1 of muramic acid, to a C55 undecaprenyl carrier. PBP1b has been puri®ed in the form of His tag (M46-N844) PBP1bg. This derivative provides the host cell in which it is produced with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
218
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(237 citation statements)
references
References 39 publications
19
218
0
Order By: Relevance
“…These results suggest that E83, and to a lesser extent D84, play important roles in the catalytic mechanism. Consistent with our findings, Terrak et al (16) have identified the invariant glutamate residue in conserved sequence motif 1 as critical for catalysis by the PGT domain of E. coli PBP1B.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that E83, and to a lesser extent D84, play important roles in the catalytic mechanism. Consistent with our findings, Terrak et al (16) have identified the invariant glutamate residue in conserved sequence motif 1 as critical for catalysis by the PGT domain of E. coli PBP1B.…”
Section: Resultssupporting
confidence: 93%
“…The kinetic parameters for the WT enzyme are k cat ϭ 3.5 min Ϫ1 and k cat /K m ϭ 6 ϫ 10 5 M Ϫ1 ⅐min Ϫ1 . This truncated PGT domain thus has comparable activity to the most efficient PGT studied to date, full length E. coli PBP1B (16,21,22), which contains the transmembrane helix and the TP domain. Activity was not detectable for either the E83 or the D84 mutant (E83A, E83Q, D84A, and D84N) under our standard assay conditions, which can only detect turnover greater than 0.04 min Ϫ1 ; however, turnover was observed for D84N, but not E83Q, at high enzyme concentrations and extended reaction times.…”
Section: Resultsmentioning
confidence: 88%
“…in the putative C-terminal extension of PBP1b of E. coli, resulted in a protein devoid of penicillinbinding activity [24]. Through construction of a series of deletion mutants of high-molecular-mass PBPs, such as PBP1b [11] and PBP3 [10] of E.coli, PBP2h of Staphylococcus aureus [25] and PBP5 of Enterococcus hirae [26], it has been postulated that acquisition of a conformation of the PB module that is competent to bind benzylpenicillin requires the presence of the n-PB module in the case of the multimodular high-molecular-mass PBPs. Our studies with PBP1 of M. leprae demonstrated that the PB module is capable of binding benzylpenicillin independently of the n-PB module.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present evidence that a membrane-associating domain, in addition to the non-cleavable pseudo-signal peptide, exists between residues 147 and 314, a feature common to two other high-molecular-mass PBPs of class A, namely PBP1b of E. coli [15,16] and PBP2a of Streptococcus pneumoniae [17]. Unlike PBP1b of E. coli [11], the C-terminal PB module of PBP1 can function as a soluble, penicillin-binding entity independent of the N-terminal non-PB module.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation